The day-to-day effects of strong geomagnetic disturbances on the North Atlantic Oscillation in the winter periods of years 1951-2003 - Bochníček, Josef; Šimkanin, Ján; Hejda, Pavel; Huth, Radan (Studia Geophysica et Geodaetica)
The day-to-day effects of the strong geomagnetic disturbances on geopotential heights (GPH) in the winter lower atmosphere were described in many papers in the beginning of 1970s. These works focused on the North-East Pacific, while the North Atlantic was until now omitted. Our aim is therefore to investigate the possible effect of strong geomagnetic disturbances on the lower atmosphere GPH changes over the winter North Atlantic on the day-to-day time scale, represented by the daily index of the North Atlantic Oscillation (NAO). The investigated intervals are winter periods (December-March) of 1951–2003. The daily NAO average values in 3-day intervals before and after the disturbance onsets are compared. The graphs of NAO differences are complemented by the maps of GPH differences. The NAO response to geomagnetic disturbance, as registered on the day-to-day time scale, also shows a change in its behaviour around the year 1970. This response reaches its highest values in the years 1951–1969, usually 2–5 days following the onset of geomagnetic disturbances. Intensity of the response depends on the disturbance intensity (the largest differences were associated with extremely strong disturbances).